Seizing Social Media Accounts Based on Indonesia and the Netherlands Comparative Criminal Procedure Law - Sabrina, Nahdiya; Hardinanto , Aris; Kumalah, Indah (Jurnal Cakrawala Hukum, 2025)
Investigators to prove the existence of a crime using social media as an intermediary, need to seize objects in the context of cybercrime, which are devices containing social media accounts. Seizure of objects related to criminal acts is regulated in the Code of Criminal Procedure. It becomes a problem whether social media can indeed be classified within the scope of the meaning of objects so that it can be seized. This research is conducted to determine whether social media accounts can be classified as objects under the Criminal Procedure Code regarding the seizure of objects that can be seized. The research methodology used to write this article employs a normative legal research methodology. The results of this study indicate that a person’s social media account cannot be seized because a social media account is not considered an object and does not fall into the classification of objects that can be subject to ownership rights. Seizure of social media accounts cannot be carried out either because it doesn’t meet the material requirements in the Criminal Procedure Code. Although social media accounts cannot be classified as objects, investigators can terminate access to the account belonging to the perpetrator with the owner.